Assessment of Irrigation Practice in Wheat at Farmers' Fields under Shallow Water Table Conditions through Simulation Model - Singh, Rajinder; Kumar, Rakesh; Kumar, Jitender (Journal of Agricultural Engineering, 2007)
The central and western part of Haryana underlain with brackish ground water quality has experienced rise of water table at a rate of 10 to 30 cm annually during the last three decades. On an average the area under critical water table depth (0-3.0 m) increased from 6.20 per cent in October 2002 to 10.61 percent in October 2003 and 10.27 per cent in October 2004. At present about 2 per cent area of the State is fully waterlogged (0-1.5m). Poor irrigation and drainage management and inadequate exploitation of saline ground water are the main factors responsible for this phenomenon. Physical based one-dimensional simulation model SWAP(Soil Water Atmosphere Plant) was employed to evaluate irrigation practice in wheat crop under shallow water table condition using field experimental data collected at farmers' fields. The field experiments were undertaken during rabi 2002-03 and 2003-04 at two sites having ground water quality EC = 4.5 and 5.5 dSm?Â¹ for site 1 and site 2 respectively and different soil types (clay loam for site 1 and loam for site 2). The water table depth varied from 100-175 cm and 70-170 cm at site 1 and site 2 respectively during the crop growth season. Simulations were undertaken for both the sites to evaluate the impact of adopted irrigation practice by the farmers on crop performance and soil salinization/desalinization processes. The model provided all water and salt balance components during crop growth season. The water and salt balance component obtained for each simulation were used to derive Water Management Response Indicators (WMRI's) (Relative Evapotranspiration, Moisture Storage Change, Salinity Hazard Index and Saturation Index). The WMRI's were further used to evaluate the performance of the crop, changes in soil moisture storage and soil salinity under the shallow water table condition. The perusal of WMRI's indicated that the soil moisture in 0-2 m profile remained on higher side during crop season at both the experimental sites (Saturation Index = 0.75 to 0.86 for site 1 and 2 respectively). The simulation study further revealed that the crop performance was good at site 1 as indicated by relatively higher Relative Evapotranspiration (0.7) and low Salinity Hazard Index (0.65) but it was relatively poor at site 2 (Relative Evapotranspiration = 0.60 and Salinity Hazards Index = 0.9) due to late sown condition. It was suggested that provision of surface and sub-surface drainage system coupled with efficient irrigation application at farmers' fields could result in sustainable crop production by maintaining desirable soil moisture and solute concentration in the profile.